Star-shaped block copolymers by copper-catalyzed azide-alkyne cycloaddition for potential drug delivery applications - Von Der Ehe, Christian; Kempe, Kristian; Bauer, Marius; Baumgaertel, Anja; Hager, Martin D.; Fischer, Dagmar; Schubert, Ulrich S. (Macromolecular Chemistry and Physics, 2012)
Star-shaped poly(μ-caprolactone) is synthesized by ring-opening polymerization and subsequently functionalized with alkyne groups. These are utilized for the attachment of linear poly(ethylene glycol) monomethyl ether azide (mPEG-N 3) and poly(2-ethyl-2-oxazoline) azide (PEtOx-N 3) by copper-catalyzed azide-alkyne cycloaddition (CuAAC). The resulting amphiphilic star-shaped block copolymers are characterized by SEC, MALDI-TOF mass spectrometry, NMR spectroscopy, and DLS. In order to elucidate the potential of both systems as drug carriers their loading capacity is studied with a model system, the hydrophobic dye fat brown RR. Furthermore, erythrocyte aggregation tests provide first indications that the two different star-shaped block copolymers are compatible for potential applications in a biological context. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2020-10-13
Keywords: CuAAC; micelles; poly(μ-caprolactone)s; poly(2-ethyl-2-oxazoline)s; star polymers